2018
DOI: 10.3892/mmr.2018.9174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric stimulation on human chondrocytes and mesenchymal stem cells under normoxia and hypoxia

Abstract: During joint movement and mechanical loading, electric potentials occur within cartilage tissue guiding cell development and regeneration. Exposure of cartilage exogenous electric stimulation (ES) may imitate these endogenous electric fields and promote healing processes. Therefore, the present study investigated the influence of electric fields on human chondrocytes, mesenchymal stem cells and the co-culture of the two. Human chondrocytes isolated from articular cartilage obtained post-mortally and human mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 47 publications
(64 reference statements)
2
51
1
Order By: Relevance
“…A decrease in cell proliferation was observed after 2 and 7 days of stimulation, while an increase cell population was evidenced after 14 days of stimulation compared with controls. This finding contrasts with previous reports, which have not noticed that MSCs cultured in micromass and collagen scaffolds do not proliferate after 7 days of electrical stimulation [341], [343], [354]. However, it has been evidenced that short exposure times of electrical stimulation increased the proliferation rate of MSCs growth in monolayer in presence of chondrogenic medium [340].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…A decrease in cell proliferation was observed after 2 and 7 days of stimulation, while an increase cell population was evidenced after 14 days of stimulation compared with controls. This finding contrasts with previous reports, which have not noticed that MSCs cultured in micromass and collagen scaffolds do not proliferate after 7 days of electrical stimulation [341], [343], [354]. However, it has been evidenced that short exposure times of electrical stimulation increased the proliferation rate of MSCs growth in monolayer in presence of chondrogenic medium [340].…”
Section: Discussioncontrasting
confidence: 92%
“…Some literature reports have evidenced that micro-mass cultures of MSCs stimulated with 20 mV/cm at 1 and 60 kHz experienced an increase in SOX-9, aggrecan and collagen type II; however, the increase in gene expression was obtained under chondrogenic conditions using TGF-β3 [341], [343]. A recent study showed that MSCs encapsulated in bovine collagen-based scaffolds and stimulated with direct coupled EFs for seven days had weaker response regarding the expression of cartilage matrix proteins [354]. These results suggest that the stimulated HA-GEL injectable hydrogel here presented is a very good alternative to induce chondrogenic differentiation not only in the absence of exogenous factors, but also in the presence of a biophysical stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…[ 128 ] Electro‐stimulation increases the expression of collagen type II mRNA and aggrecan mRNA in human chondrocytes and mesenchymal stem cells, further supporting a role in tissue repair. [ 129 ]…”
Section: Electro‐stimulation and The Development Of Conductive Bioscamentioning
confidence: 99%
“…Exogenous-cell-based therapy is gaining traction for the regeneration of articular cartilage over stimulation therapy such as electric stimulation of endogenous cartilage growth factors [ 97 ]. Exogenous cell therapy can be done through the delivery of chondrocytes (either autologous or allogeneic), mesenchymal stem cells (MSCs), or extracellular vesicles [ 98 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…MSCs are used for regenerative medicine due to their ability to promote regeneration based on environmental signals at sites of injury. As inhibitors of the immune system and multilineage differentiators, MSCs are an important alternative cell source for articular cartilage repair and regeneration [ 97 ]. MSCs derived from the synovial membranes of joints have been shown to be more effective in terms of articular cartilage formation in in vitro studies when compared to MSCs from other tissues, joint and nonjoint [ 99 , 100 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%